Planning for Quality Interior Design Creations - Duangsamran , Khattipong (Arts of Management Journal, 2021)
Interior design that leads to quality work. It has to be planned for success with creative factors in all dimensions of that work. It makes an impression on investors or witnesses. Therefore, need to understand the process and having principles of interior design in its entirety, every element, every context around the direction is useful. The beauty of form and layout and psychology of interior design. The professional practice in interior designer must meet the new needs of society and the context changed and must develop themselves to be qualified personnel of young interior designers to create good quality work and systematic. By applying the PDCA quality cycle applied in planning to produce works creatively and with quality. Which is the Important basis for efficient interior design and passed the standards set by the professional field.